2020
DOI: 10.3390/su12031098
|View full text |Cite
|
Sign up to set email alerts
|

Grazing of Dairy Cows in Europe—An In-Depth Analysis Based on the Perception of Grassland Experts

Abstract: Grazing is inherently close to the nature of herbivores, but no longer applied everywhere in Europe. Therefore, the perception of grassland experts on the occurrence, importance, constraints, solutions and future of grazing of dairy cows was studied. The study builds on results from the European Grassland Federation Working Group Grazing in the period 2010–2019. Both surveys and focus group meetings were used. There is a clear trend of reduced grazing in Europe. Since grazing is valued by different stakeholder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 27 publications
2
63
0
Order By: Relevance
“…and duration of access (i.e., days per year and hours per day). In 2019, pasture access in Europe was estimated to range from 95-100% of dairy cows in Ireland, to <25% in Denmark, Poland, and Greece, with most other countries being intermediate [for an overview, please see (12)] (n.b. these figures do not distinguish between farms that provide cows free choice access to pasture from a barn vs. cows housed exclusively outdoors).…”
Section: Europementioning
confidence: 99%
See 2 more Smart Citations
“…and duration of access (i.e., days per year and hours per day). In 2019, pasture access in Europe was estimated to range from 95-100% of dairy cows in Ireland, to <25% in Denmark, Poland, and Greece, with most other countries being intermediate [for an overview, please see (12)] (n.b. these figures do not distinguish between farms that provide cows free choice access to pasture from a barn vs. cows housed exclusively outdoors).…”
Section: Europementioning
confidence: 99%
“…Data from The Netherlands indicates that in 2018, 71% of the dairy cows aged 2 years and older had access to pasture (13); duration of pasture access was not specified. Regardless, the general trend in the majority of European countries is that the number of farms providing cows with pasture access is declining (12). The exception being some of the nordic countries, such as Sweden, Norway, and Finland, that have implemented regulations requiring farms to provide dairy cows access to pasture for specified periods (12).…”
Section: Europementioning
confidence: 99%
See 1 more Smart Citation
“…Carbon footprint (CF) is entirely referred to global warming potential (GWP) and it is commonly used to communicate the contribution of dairy production to climate change to stakeholders [13]. Dairy farming in the Italian Alps has transformed greatly in the last decades; between 1990 and 2010, farms declined by 60%, while the number of cows decreased by 29%, with a growth of the average herd size by 76% [14][15][16]. Many of these farms have abandoned traditional Alpine pasture practices by increasing the amount of concentrated feed purchased off-farm.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown the link between improved grazing management performance and overall farm business performance (Fariña & Chilibroste, 2019;Hanrahan et al, 2018;Neal & Roche, 2020). However, these systems require specific skills in managing pastures within dynamic biological and climate environments Turner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%